2007
DOI: 10.1186/1471-2164-8-354
|View full text |Cite
|
Sign up to set email alerts
|

Expression and water calcium dependence of calcium transporter isoforms in zebrafish gill mitochondrion-rich cells

Abstract: Background: Freshwater fish absorb Ca 2+ predominantly from ambient water, and more than 97% of Ca 2+ uptake is achieved by active transport through gill mitochondrion-rich (MR) cells. In the current model for Ca 2+ uptake in gill MR cells, Ca 2+ passively enters the cytosol via the epithelium Ca 2+ channel (ECaC), and then is extruded into the plasma through the basolateral Na + / Ca 2+ exchanger (NCX) and plasma membrane Ca 2+ -ATPase (PMCA). However, no convincing molecular or cellular evidence has been ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 53 publications
9
90
0
Order By: Relevance
“…Recently in zebrafish ECaC has been cloned and characterized to be responsible for Ca 2þ uptake in the gill MR cells. (6) Our results lead us to conclude that there is a hypocalcemic role for CT, probably through the inhibition of ECaC synthesis. Furthermore, this study suggests that this hypocalcemic role of CT could be conserved throughout zebrafish development and still be present in adults.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently in zebrafish ECaC has been cloned and characterized to be responsible for Ca 2þ uptake in the gill MR cells. (6) Our results lead us to conclude that there is a hypocalcemic role for CT, probably through the inhibition of ECaC synthesis. Furthermore, this study suggests that this hypocalcemic role of CT could be conserved throughout zebrafish development and still be present in adults.…”
Section: Discussionmentioning
confidence: 74%
“…In zebrafish, epithelial Ca 2þ channels (ECaC), NCX1b, and PMCA2 have been shown to be specifically expressed in a group of ionocytes (mitochondria-rich [MR] cells) and be involved in transepithelial Ca 2þ uptake. (3)(4)(5)(6)(7) Different hormones participate in the control and regulation of calcium homeostasis. In mammals, the three main hormones involved in the calcium regulation are parathyroid hormone (PTH), vitamin D, and calcitonin (CT).…”
Section: Introductionmentioning
confidence: 99%
“…All these suggest that ECaC is the rate-limiting step and the gatekeeper channel for active Ca 2+ transport in fish as in mammals (Vennekens et al, 2000). Acclimation to low-Ca 2+ FW caused upregulation of zECaC but not zPMCA2 or zNCX1b, implying that the steady-state expression of zPMCA2 and zNCX1b may fulfill the requirement for the transepithelial transport machinery under all situations (Liao et al, 2007). This further supports a previous enzyme kinetic study, in which the basolateral Ca 2+ extrusion mechanisms by PMCA and NCX were found to be far below their maximum capacity in rainbow trout (Oncorhynchus mykiss) gills (Flik et al, 1997).…”
Section: Nar Cellsmentioning
confidence: 99%
“…Taken together, it may be that only PNA + cells express ECaC and basolateral transporters (PMCA and NCX) and thus can achieve the entire transepithelial Ca + pathway, although no data for the existence PMCA and NCX in trout gill cells are available so far. Indeed, it was also found that not all ECaC-expressing cells coexpressed both zPMCA2 and zNCX1b in zebrafish gill NaR cell populations (Liao et al, 2007), which may be analogous to trout PNA + cells (see below). Fish gill cells that express only one or two (never all) of the three major Ca 2+ transporters may be in the process of terminal differentiation as Hsiao and coworkers (Hsiao et al, 2007) reported in zebrafish embryonic skin ionocytes.…”
Section: Nar Cellsmentioning
confidence: 99%
See 1 more Smart Citation